If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + x = 90 Solving 3 + x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 90 + -3 Combine like terms: 3 + -3 = 0 0 + x = 90 + -3 x = 90 + -3 Combine like terms: 90 + -3 = 87 x = 87 Simplifying x = 87
| {4}=3 | | 8x^2-66x+81=0 | | 3+6y=9 | | 0+3n=7 | | x=277 | | 5=3+6 | | 3x^2+7=7x | | 40d+60d=20d | | 2-3y=11 | | X+Y=X+Y+10 | | -2+3n=7 | | 100=-1c+5c | | 8(5x-3)=32x | | .75y-6=4y+10 | | 3x/4+5=x/2+7 | | 3*3/4-3/2-5=7 | | 3*3/4-3/2-5= | | 2x^2+14-60=0 | | 3*48/4-48/2-5= | | XY=X+Y+10 | | 2sin(x+pi)=0 | | 100c+1c=5c | | 3y/4-y/2-5=7 | | 3y/8-6=y/4-5 | | X/2-x/3+x/4=5 | | 6x^2-15x-1=0 | | 8-4x=26-13x | | x^2+7x-35=0 | | 8+8C=6C+88 | | 141-5x=3x+22 | | (1/4)(6x+1)=4x | | 3(y-1)+20=5+3(y+5) |